OP21 Cognitive performance and history of multiple health conditions in older adults. (3rd September 2019) - Bendayan, R; Dobson, RJ
Abstract : Background: Multimorbidity, defined as the coexistence of two or more health conditions, is becoming the norm in our ageing population. Research to date has highlighted that individuals with multiple health conditions are at greater risk of disability and mortality, but also of cognitive impairment and dementia. Most of research to date on multimorbidity and cognitive performance is cross-sectional or with limited history information of the health conditions. The present study aims to explore the association between cognitive performance and previous history of health conditions over 24 years. Methods: The sample consisted of 4858 respondents of the Health Retirement Study (HRS), which is a US nationally representative survey that focus on adults aged 50 and over. Data was extracted from 12 consecutive waves from 1998 to 2014. Data from health conditions included self-reports for hypertension, diabetes, arthritis, stroke, cancer, lung and heart diseases and psychiatric problems. Duration of the health condition was categorized as more than 10 years, between 4 and10 years, less than 4 years and no condition. Cognitive status was assessed using a summary index of cognitive functioning which includes measures of memory, working memory, speed of mental processing, knowledge, and language. ANOVA and post hoc tests were performed to explore the association between cognition and the duration of each health condition independently. Multiple linear regression analyses were performed to explore the association between multiple health conditions and cognitive performance. Results: The results showed significant independent associations between cognitive performance in 2014 and each health condition independently, except for cancer [F (1, 4)=2.60; p=0.51]. When all the health conditions were considered together in the regression models, we found that cognitive performance is negatively associated with high blood pressure and stroke (independently of the duration of the condition), long-term diabetes and lung diseases (i.e., for more than 10 years) and recent cancer (i.e., in the last 4 years). Conclusion: Our results confirm that cognitive performance is significantly lower in older adults with multiple health conditions. Moreover, our findings highlight that considering the duration of the health condition is key for identifying patients at greater risk of cognitive impairment. Specifically, individuals at greater risk of cognitive impairment are those who have been diagnosed with hypertension or suffered a stroke at any given time, long-term diabetes or lung diseases, and recent cancer diagnoses. Public health makers should develop specific policies for cognitive screening in individuals with these health conditions.